Differential Object Marking in Tukano - Lopes, Braulio Brandão de Oliveira; Duarte, Fábio Bonfim (Revista Letras, 2021)
The main purpose of this paper is to demonstrate that the Tukano language exhibits differential object marking, hereafter DOM. It also assumes that the occurrence of the overt morphological Case marking {-re} has the role of indicating whether the internal argument is definite or not, thereby being responsible for activating DOM in Tukano. This hypothesis is based on the fact that this Case marker only appears in definite objects, never in indefinite objects. Furthermore, based on the Dependent Case Theory proposed by Baker (2015), this paper proposes the hypothesis that {-re} is the morphological instantiation of the low dependent Case that is assigned to internal arguments in the CP-TP-vP domains. We also propose that the syntactic distribution of this suffix can be readily explained by the application of the dependent Case assignment rule, as is posited by Baker (2015).